Project-Based Learning as a Transformative Approach to Enhancing EFL Students’ Paragraph Writing Competence - Ajam, Ali; Daud, Abdulhalim; Lestari, Sri Ayu Budi; Rizal , Awaludin; Wahid, Jusmin HJ (Universitas Sulawesi Barat, 2026)
This study investigates the effectiveness of project-based learning (PBL) in enhancing the paragraph writing skills of first-year college students. A total of thirty-one students participated in the research, which utilized a pre-test and post-test design to objectively measure improvements resulting from the instructional intervention. The data collected from both tests were analyzed using SPSS, with descriptive statistical methods applied to evaluate the outcomes. The findings reveal a clear advancement in students’ writing skills following their engagement in project-based learning activities. The mean score for the pre-test was 67.48, while the post-test mean increased to 75.64. This significant improvement suggests that PBL has a positive impact on students’ ability to construct coherent and effective paragraphs. The collaborative nature of PBL was also evident, as students worked together in groups, leveraging a project-based learning assistant to guide them through the writing process. They engaged in drafting, revising, and refining their paragraphs, with particular focus on building strong arguments and supporting them with relevant facts and references. The collaborative environment encouraged peer learning and mutual support, promoting greater engagement and a sense of responsibility among group members. These initial results provide a valuable baseline for future research and instructional practices. They illustrate how project-based learning can not only enhance students’ writing abilities but also cultivate essential skills such as teamwork, analytical thinking, and effective communication. The outcomes of this study suggest that integrating PBL into writing instruction may be a promising approach for educators seeking to improve students’ academic writing performance and foster active, collaborative learning environments.